Trading options : using technical analysis to design winning trades - Harmon, Greg (John Wiley & Sons, Inc., 2014)
A thorough guide to technical analysis methods applied for success in the options market Though still not widely practiced or accepted in the options market, technical analysis is becoming increasingly common. As the practice spreads, traders are discovering how useful technical analysis is for determining clear entry and exit signals. Trading Options: Using Technical Analysis to Design Winning Trades takes the standard technical analysis approach and applies it to the options market. Author Greg Harmon combines technical analysis with a deep understanding of the options market to explain how.